SOCIAL NETWORK A CATALYST FOR OPPORTUNITY IDENTIFICATION: A STUDY OF NASCENT ENTREPRENEURS IN OSUN STATE, NIGERIA - Tund, Odebunmi Abayomi; Kee, Daisy Mui Hung (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to examine the social network in Osun State, Nigeria as a tool for the discovery of opportunities by budding entrepreneurs. Given the fact that the field of nascent entrepreneurs has received much attention from stakeholders, in the sense of Nigeria there is a limited amount of empirical work on nascent entrepreneurs. The study was using analysis concept from the survey. The research population was 291 Nascent business people in Osun State, Nigeria. Random sampling technique was employed in study and 251 questionnaire was administered and returned full. Data was analyzed through the Smart-PLS. The finding reveals the relationship between the bonding ties and bridging ties on opportunity recognition is mediated by knowledge. the findings also show that bridging ties is a good predictor of finding prospects as opposed to bonding ties. Accordingly, the study concludes that identifying opportunities is an uninterrupted cycle that supports a venture's pre-start, survival and growth so, concentrating more on bonding links and bridging relations as they have a major effect on identifying opportunities.